Enhancement of Th1 immune responses to recombinant influenza nucleoprotein by Ribi adjuvant - Cargnelutti, Diego Esteban (2013)
A broad coverage influenza vaccine against multiple viral strains based on the viral nucleoprotein (NP) is a goal pursued by many laboratories. If the goal is to formulate the vaccine with recombinant NP it is essential to count on adjuvants capable of inducing cellular immunity. This work have studied the effect of the monophosphoryl lipid A and trehalose dimycolate, known as the Ribi Adjuvant System (RAS), in the immune response induced in mice immunized with recombinant NP. The NP was formulated with RAS and used to immunize BALB/c mice. Immunizations with NP-RAS increased the humoral and cellular immune responses compared to unadjuvanted NP. The predominant antibody isotype was IgG2a, suggesting the development of a Th1 response. Analysis of the cytokines from mice immunized with NP-RAS showed a significant increase in the production of IFN-gamma and a decreased production of IL-10 and IL-4 compared to controls without RAS. These results are similar to those usually obtained using Freund´s adjuvant, known to induce Th1 and CTL responses when co-administered with purified proteins, and suggest that a similar approach may be possible to enhance the performance of a T-cell vaccine containing NP.